2011
DOI: 10.1002/chin.201202102
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Aryl Halomethylated Unsaturated Iminolactones (IV)

Abstract: Synthesis of Aryl Halomethylated Unsaturated Iminolactones (IV) -[via microwave assisted multi-component reactions under solvent free conditions]. -(ZONOUZI*, A.; RAHMANI, H.; BINIAZ, M.; IZAKIAN, Z.; NG, S. W.; J. Chem. Res. 35 (2011) 7, 412-415, http://dx.doi.org/10.3184/174751911x13099687368563 ; Sch. Chem., Coll. Sci., Univ. Tehran, Tehran, Iran; Eng.) -A. Forchert 02-102

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In continuation of our research in the field of organic compounds, [ 5 ] and our quest to develop novel synthetic approaches of chromene derivatives, [ 6 ] herein we wish to report a new approach for the synthesis of fused 2,8‐dioxabicyclo[3.3.1]nonane to barbituric acid moiety via a domino reaction without using any expensive catalyst. In brief, chromene derivatives 2 are initially produced by condensation of 2‐hydroxy benzaldehydes 1 and 2,4‐pentandione (acetylacetone) [ 6a ] then used as starting material to condense with barbituric and thio barbituric acid 3 , which yields compounds 4 in a one‐pot manner. In Scheme 1, synthetic method and the evaluated V‐shape X‐ray structure of the final product have been shown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In continuation of our research in the field of organic compounds, [ 5 ] and our quest to develop novel synthetic approaches of chromene derivatives, [ 6 ] herein we wish to report a new approach for the synthesis of fused 2,8‐dioxabicyclo[3.3.1]nonane to barbituric acid moiety via a domino reaction without using any expensive catalyst. In brief, chromene derivatives 2 are initially produced by condensation of 2‐hydroxy benzaldehydes 1 and 2,4‐pentandione (acetylacetone) [ 6a ] then used as starting material to condense with barbituric and thio barbituric acid 3 , which yields compounds 4 in a one‐pot manner. In Scheme 1, synthetic method and the evaluated V‐shape X‐ray structure of the final product have been shown.…”
Section: Introductionmentioning
confidence: 99%
“…In the present research, 2 H ‐chromene 2 was characterized as an intermediate; we have already reported a simple procedure for the synthesis of 2 using 2‐hydroxy benzaldehydes 1 and acetylacetone in the presence of piperidine base in CH 2 Cl 2 as solvent. [ 6a ] In order to optimize the procedure and propose the mechanism, synthesis of 4a using 2 H ‐chromene 2a and barbituric acid 3a has been considered; the results are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation